2021
DOI: 10.13057/biodiv/d220304
|View full text |Cite
|
Sign up to set email alerts
|

The potency of actinomycetes extracts isolated from Pramuka Island, Jakarta, Indonesia as antimicrobial agents

Abstract: Abstract. Setiawati S, Nuryastuti T, Sholikhak EN, Lisdiyanti P, Pratiwi SUT, Sulistiyanti TR, Ratnakomala S, Jumina, Mustofa. 2021. The potency of actinomycetes extracts isolated from Pramuka Island, Jakarta, Indonesia as antimicrobial agents. Biodiversitas 22: 1104-1111. Actinomycetes are one of the Gram-positive bacteria which are widely distributed and produce many secondary metabolites including those known as antibiotics, antifungals, anticancer, and antimalarials agents. The secondary metabolites of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Another study found one isolate (InaCC A765) of three Actinomycetes isolates from a sand beach in Pramuka Island, Kepulauan Seribu, Jakarta, Indonesia, had antimicrobial activity against S. aureus ATCC 6538, B. subtilis BTCC B-612, and E. coli BTCC B-614, with zones of inhibition measuring 20, 18 and 20 mm, respectively. InaCC A765 is closely related to Nocardia otitidiscaviarum Snijders 1924 strain NBRC 14405 (MN826189); it has a similarity of 96.06% (Setiawati et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found one isolate (InaCC A765) of three Actinomycetes isolates from a sand beach in Pramuka Island, Kepulauan Seribu, Jakarta, Indonesia, had antimicrobial activity against S. aureus ATCC 6538, B. subtilis BTCC B-612, and E. coli BTCC B-614, with zones of inhibition measuring 20, 18 and 20 mm, respectively. InaCC A765 is closely related to Nocardia otitidiscaviarum Snijders 1924 strain NBRC 14405 (MN826189); it has a similarity of 96.06% (Setiawati et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces koyangensis SHP 9-3 from the solid medium was inoculated into 100 mL of ISP-2 and incubated for 72 hours at 30°C and 130 rpm in a shaker incubator (Setiawati et al 2021). Afterward, 90 mL of production medium and 10 mL of pre-culture stock were added to a 500 mL baffled flask (Susanti et al 2019).…”
Section: Production Of Secondary Metabolitesmentioning
confidence: 99%
“…Antibiotic resistance is still a global concern in the health sector (Jakubiec-Krzesniak et al 2018;Atikana et al 2021;Setiawati et al 2021). Approximately 700,000 people die annually from infectious diseases and drug resistance (Ragheb et al 2019).…”
Section: Introductionmentioning
confidence: 99%